Hackh's chemical dictionary : [American and British Usage ] ; Containing the Words Generally Used in Chemistry, and Many of the Terms Used in the Related Sciences of Physics, Astrophysics, Mineralogy, Pharmacy, Agriculture, Biology, Medicine, Engineering, etc. Based on Recent Chemical Literature - Hackh, Ingo Waldemar Dagobert (McGraw-Hill Book Company, 1969)
Almost 55,000 words are defined, including most new words created during the 25 years since the last edition. 3d ed., 1944.